Fabrication and characterization of open cell inconel alloy 625 foams - Ho, Ninian Sing Kok (2016)
Open cell metal foams possess an unusual combination of properties, and have thus been identified to be particularly suitable for a variety of applications. However, current methods to produce them successfully are few, and each only caters to a certain metal alloy. In this study, a novel slurry coating method was developed that can produce open cell Inconel alloy 625 foams of varying pore sizes. For a selected pore size, the effects of two fabrication parameters, namely slurry composition and sintering time, on the foam mechanical properties and microstructure were investigated. An acoustic test was later conducted on two Inconel foams of different pore sizes to investigate the effect of pore size on sound absorption coefficient for sound frequencies between 800 Hz and 6300 Hz. The open cell nature of the Inconel foam was verified using a quick X-ray CT scan. This study has found that for the fabricated Inconel foams, an increase in Inconel powder mass used in the slurry leads to an increase in bulk density of the final Inconel foam product, while an increase in sintering time from two to six hours does not cause a significant change in bulk density. Furthermore, bulk density was found to be related to compressive strength, plateau stress and Young’s Modulus by the well-known empirical relationships published by Ashby et al with 2 values of 0.8198, 0.8784 and 0.9404 respectively when twelve samples were tested. For the acoustic test, results obtained were similar to those published by Han et al for open cell aluminium foams. Between the two foams that were tested, the foam with the smaller average pore size had its reaching a maximum value of 0.67 at about 2500 Hz and was the better performing foam. To conclude, this new slurry coating method is capable of producing open cell Inconel 625 foams with higher compressive strength compared to currently available open cell foams made of similar alloys. It has been developed to work on several brands of sacrificial polyurethane templates, though it shows the most promise with the Regicell series of template used by Matz et al in a previous study. For a given template, bulk density was successfully controlled by the adjustment of the slurry composition.